Fundamentals of radiation and chemical safety - Obodovskiy, Ilya (Elsevier, 2015)
Fundamentals of Radiation and Chemical Safety covers the effects and mechanisms involved in radiation and chemical exposure on humans. The mechanisms and effects of these damaging factors have many aspects in common, as do their research methodology and the methods used for data processing. In many cases of these types of exposures the same final effect can also be noted: Cancer. Low doses of radiation and small doses of chemical exposure are continuously active and they could influence the entire population. The analysis of these two main source hazards on the lives of the human population. The analysis of these two main source hazards on the lives of the human population is covered here for the first time in a single volume determining and demonstrating their common basis. Fundamentals of Radiation and Chemical Safety includes the necessary knowledge from nuclear physics, chemistry and biology, as well the methods of processing the experimental results. Intended for students, graduate students and professionals in the fields of physics, chemistry, biology, ecology, and a range of interdisciplinary sciences. The book can also be used by practitioners as a reference in order to find more detailed information on special issues of radiation and chemical safety. Tis title focuses on the effects of low radiation dosage and chemical hormesis as well as the hazards associated with, and safety precautions in radiation and chemicals, rather that the more commonly noted safety issues high level emergencies and disasters of this type.
Keywords: Hazardous substances -- Safety measures.; Radiation -- Safety measures.; Chemicals -- Safety measures.; Ionizing radiation.; elektronické knihy; electronic books